Seeking a measure of clinically meaningful change in ALS. Issue 5 (September 2014) - McElhiney, Martin; Rabkin, Judith G.; Goetz, Raymond; Katz, Jonathan; Miller, Robert G.; Forshew, Dallas A.; David, William; Cudkowicz, Merit; Glass, Jonathan D.; Appel, Stanley; Simpson, Ericka; Mitsumoto, Hiroshi
Abstract We sought to identify a method to assess 'clinically meaningful change' perceived by patients, caregivers and clinical raters in relation to changes in ALSFRS-R scores at three-month intervals. In this five-site study, 81 patient-caregiver dyads were interviewed at baseline, three, and six months to assess changes in ALSFRS-R in relation to perceived occurrence of change, its magnitude and impact. Ratings by patients, caregivers and clinical raters were analyzed over three-month intervals within and between respondent groups. We found that patients, clinical raters, and caregivers agreed about 80% of the time about whether change occurred, and in what direction, on each of three visits. The perceived magnitude of change for the four domains measured by the ALSFRS-R was correlated with ratings of impact within respondent groups and across time. We also found moderate associations between changes in ALSFRS-R domain scores and judgments of symptom impact as rated by patient, caregiver and clinical rater. Independent measures (Quality of Life, Goal Assessment Scaling) showed no consistent correlations with ALSFRS-R change scores. In conclusion, the use of scales to assess the perceived magnitude and impact of change corresponding with the domains of the ALSFRS-R may be a step towards understanding of the clinical meaning of changes in that measure.